Readiness of Independent Oil Palm Farmers to Face Replanting - vanika lestari; Dolorosa, Eva; Komariyati (INDONESIAN JOURNAL OF SMALL SCALE FARMING, 2026)
BACKGROUND AND OBJECTIVESOil palm has an average productive life of about 25 years, after which yields decline. Replanting is therefore essential to sustain long-term productivity. This study examines the readiness of independent oil palm farmers and identifies the main factors that influence their preparedness to undertake replanting in Laman Bukit Village, Belimbing District, Melawi Regency, Indonesia. METHODSThe research was conducted in Laman Bukit Village, an area with the largest oil palm plantation coverage in the regency. A total of 100 respondents were selected from 351 farming households using simple random sampling. Data were gathered using structured Likert-scale questionnaires and analyzed using descriptive statistics and Partial Least Squares–Structural Equation Modeling(PLS-SEM) with SmartPLS 4. FINDINGSThe results show that independent farmers were generally classified as prepared to implement replanting. Personal factors, ownership of other plantations, and financial conditions had a significant positive effect on readiness. In contrast, institutional f actors did not show a significant statistical effect, indicating that existing institutions have not yet functioned effectively to directly support farmers’ readiness. This indicates that strengthening local institutional capacity remains necessary. CONCLUSIONFarmers’ readiness for replanting is strongly supported by personal experience, access to alternative productive assets, and financial preparedness. Strengthening these aspects is crucial to ensure the sustainability of oil palm replanting programs.